Review: Women in plant disease management - Gullino, Maria Lodovica (Frontiers in Agronomy, 2023)
Women began to take a stance on science over 50 years ago, producing a vast number of publications; the first step towards science was a matter of accrediting women as rightful members of the scientific community. During the late nineteenth and early twentieth centuries women started entering into graduate programmes: such a step helped them to make a difference. In the discipline of plant pathology, botanists and mycologists were in some way pioneering, in many cases and countries. This manuscript considers some women who led the way in plant pathology, with special focus on those dealing also with early aspects of plant disease management. Women active in different geographical areas are considered, also trying to provide some less known stories. Moreover, the importance of women behind the scene, such as many lab and field technicians, whose lives have not been chronicled, is acknowledged. Finally, some suggestions on how to improve the present situation, increasing the number of women in science as well as in apical position, are given, with special emphasis on the positive effect of female mentors and role models.